O ESTADO DE SÃO PAULO E A DEPOSIÇÃO DO PRESIDENTE GOULART (1964): UM ESTUDO SOBRE AS PECULIARIDADES DO LIBERALISMO NO BRASIL (Revista de História Regional, 2007)
The article analyzes the liberal discourse in the editorials of the Estado de São Paulo a brazilian daily newspaper during the final crisis of President Joao Goularts administration and the installation of the military rule (1964). The article characterizes the brand of liberalism developed in Brazil, and inquires into how, in that historical context, the liberal principle of preservation of the law took shape in this daily publication. The article shows the similarities and differ-ences between the home-brand liberalism as published in Estado de São Paulo and the classical liberalism of European origin.